Topography of the deep temporal arteries and implications for performing safe aesthetic injections. (17th December 2021) - Nikolis, Andreas; Enright, Kaitlyn M.; Troupis, Theodore; Koutsilieris, Michael; Stratigos, Alexander J.; Rigopoulos, Dimitrios; Cotofana, Sebastian
Abstract: Background: Several studies have started investigating the safety of temporal rejuvenation using soft tissue fillers. However, as the temporal region is highly vascularized, adverse events due to intravascular injection are of primary concern. The scarcity of treatment guidelines to date have focused primarily on avoiding the superficial and middle temporal arteries. The aim of the present anatomical study was to describe the topography of the deep temporal arteries (DTAs) with reference to superficial landmarks, to aid clinicians who perform temporal injections. Methods: The tissue layers of eight fresh‐frozen cephalic cadavers were dissected and assessed, bilaterally in the temporal region ( N  = 16). Distance (D) of the anterior (D1 and D3) and posterior (D2 and D4) arteries was measured from (i) the zygomaticofrontal suture line at the lateral orbital rim (D1 and D2) and (ii) the junction of the superior border of the zygomatic arch and lateral orbital rim (D3 and D4). The distance between the anterior and posterior DTAs was also recorded, at the two regions (D5). Results: Bifurcations of the DTAs were observed in 18.75% (3/16) and 12.5% (2/16) of cases, for the anterior and posterior branches, respectively. On average [mean (standard deviation)], D1 (anterior DTA to the zygomaticofrontal suture line at the lateral orbital rim) = 1.56 cm (0.59); D2 (posterior DTA to the zygomaticofrontal suture line at the lateral orbital rim) = 2.98 cm (0.70); D3 (anterior DTA to the junction of the superior border of the zygomatic arch and lateral orbital rim) = 1.14 cm (0.63); D4 (posterior DTA to the junction of the superior border of the zygomatic arch and lateral orbital rim) = 2.37 cm (0.62); and D5 (distance between the anterior and posterior DTAs) = 1.54 cm (0.68). Conclusion: To help avoid vascular adverse events while performing temporal injections, aesthetic clinicians should be conscientious of safety implications related to the anatomical location of the DTAs and their ramifications.